Use of Ultrapro(R) Mesh for Complex Mastopexy Due to Ptosis and Repeated Implant Rotation - Parra, Jairo Fernando Navarro; Álvarez, Thiago Andrés Navarro; Álvarez, Ricardo Andrés Novoa; Parra, Jaime Antonio Navarro (Journal of Posthumanism, 2025)
Mastopexy is one of the most performed aesthetic procedures. For certain cases the use of acellular dermal matrices (ADM), which have been widely used, with excellent results, for prosthetic breast reconstruction processes, is widely beneficial. Given their cost, other types of mesh have begun to be used; however, so far, no cases have been published on the use of Ultrapro® mesh for aesthetic mastopexy and even less in cases that have required reintervention. Here we describe the case of a 40-year-old woman who came for revision of her bilateral aesthetic breast pexy after multiple revision surgeries. Concerns prior to the last surgery were pain, flattening of the implant, and asymmetry. We sought the least invasive and definitive operation by placing the mesh. The operation was successful, and the patient is asymptomatic, with soft breasts and stable implant positions. The mesh is easy to fix by suture, lends itself to form a hammock that supports the implant and improves the healing process. Its efficacy in this procedure is yet to be established, so it is considered necessary to continue evaluating and comparing the results obtained with different types of mesh and in different cases of patients undergoing breast aesthetic surgery.